ابن تیمیہ متفرد کیوں؟ اسباب و علل کاتجزیاتی مطالعہ: A Research Review of the Reasons of Ibn Taymiyya’s Distinctions - Haq, Fazal (Al-Amīr Research Journal for Islamic Studies, 2020)
Ibn Taymiyya is known as a controversial figure due to his differences. Most of the scholars have differed with him on most of the jurisprudential and principled issues. There are many reasons for Ibn Tamiya’s differences. The difference between intellect and its use is the most important, that is, the way of thinking. The jurisprudential ability and competence that elevated him to the status of ijtihad was a result of uniqueness in ijtihad and jurisprudence. Disagreements can be caused by the circumstances of that era and the behavior of the people of that era. All the principles and their preferred methods based on which he solved jurisprudential and doctrinal issues and all the reasons why he disagreed with a section of the ummah and the ummah know these differences in the form of the differences of Ibn Taymiyya. It is very important that his jurisprudential insight and ijtihad efforts be revealed, although in many issues the majority of the scholars of the ummah have disagreed with him and their opinion differs from the great taste. Ibn Tamiya’s method of inference in jurisprudential and principled issues and the principles by which he formed an opinion on an issue and on what basis he preferred principles in solving problems are the key issues that will be discussed in the following article.